A study of service provision in psychocutaneous medicine. (1st January 2014) - Lowry, C. L.; Shah, R.; Fleming, C.; Taylor, R.; Bewley, A.
Summary: Background: Psychocutaneous medicine concerns the recognition and treatment of psychological distress and psychiatric morbidity associated with dermatological diseases. A study in 2004 examining resources in the UK highlighted a number of deficiencies, and recommended that psychodermatology services be available, at least regionally, in the UK. Although there is now increased recognition of psychodermatology, this study of the availability of these services shows that provision has deteriorated since 2004. Aim: To study the service provision of psychocutaneous medicine in the UK. Methods: Consultants in dermatology units across the UK were asked to take part in an online survey, accessible via an emailed link. This consisted of 10 questions concerning availability of psychodermatology services and psychological support for patients within their local trusts, both in adult and in child and adolescent medicine. Basic percentages were used to analyse quantitative data and content analysis for qualitative data. Results: From 154 surveys, 127 responses were returned. The data indicated that despite frequently encountering patients who required psychological and psychiatric input, a large majority of UK dermatologists have inadequate access to appropriate support in their department. Importantly, this included the child and adolescent medicine and skin cancer departments, despite there being clear objectives for these services to be routinely available. Conclusions: A lack of resources in psychocutaneous medicine was highlighted in 2004, and the situation has not improved, or is, if anything, worse. Essential access to psychiatric and psychological support for patients is not currently available in most dermatology departments across the country.